Bubble-template-assisted synthesis of hollow fullerene-like MoS2 nanocages as a lithium ion battery anode material. Issue 1 (9th October 2015) - Zuo, Xiaoxia; Chang, Kun; Zhao, Jing; Xie, Zhengzheng; Tang, Hongwei; Li, Bao; Chang, Zhaorong
Abstract : MoS2 nanocage anodes synthesized by a bubble-template-assisted method can provide a large expandable area to stabilize the electrode structure during cycling. Abstract : Inorganic fullerene (IF)-like structured materials have attracted considerable attention for electrochemical energy storage and conversion. In this report, we describe a facile method of synthesizing IF-MoS2 hollow structures with a diameter of ∼100 nm by a facile solution-phase reduction process to obtain a hollow MoS x precursor under ambient pressures before subsequent annealing of the material at high temperatures to form IF-MoS2 nanocages. TEM images at different reaction stages reveal the hollow structure spontaneously arising in the novel "close-edge" nanocages under the assistance of an ammonia cation bubble template. When evaluated as an anode material for lithium ion batteries, ex situ characterization indicates that these IF-MoS2 hollow nanocages can provide large expandable spaces for volume changes occurring during the cycles. Such a highly desired structure offers remarkably improved lithium storage performance including high reversible capacity and good cycling behavior and high rate capability.